Inter‐trial alpha power indicates mind wandering. (11th April 2020) - Arnau, Stefan; Löffler, Christoph; Rummel, Jan; Hagemann, Dirk; Wascher, Edmund; Schubert, Anna‐Lena
Abstract: Mind wandering during ongoing tasks can impede task performance and increase the risk of failure in the laboratory as well as in daily‐life tasks and work environments. Neurocognitive measures like the electroencephalography (EEG) offer the opportunity to assess mind wandering non‐invasively without interfering with the primary task. However, the literature on electrophysiological correlates of mind wandering is rather inconsistent. The present study aims toward clarifying this picture by breaking down the temporal dynamics of mind wandering encounters using a cluster‐based permutation approach. Participants performed a switching task during which mind wandering was occasionally assessed via thought probes applied after trial completion at random time points. In line with previous studies, response accuracy was reduced during mind wandering. Moreover, alpha power during the inter‐trial interval was a significantly increased on those trials on which participants reported that they had been mind‐wandering. This spatially widely distributed effect is theoretically well in line with recent findings linking an increased alpha power to an internally oriented state of attention. Measurements of alpha power may, therefore, be used to detect mind wandering online during critical tasks in traffic and industry in order to prevent failures. Abstract : Mind wandering is highly prevalent in our daily lives and may impede task performance. In this EEG study, participants performed a switching task during which mind wandering was assessed via thought probes. A cluster‐based permutation test revealed a spatially distributed effect in terms of an increased alpha power during the inter‐trial interval when mind wandering.